Endosonography-guided drainage of malignant fluid collections using lumen-apposing, fully covered self-expanding metal stents - Musumba, Crispin; Tutticci, Nicholas; Nanda, Kavinderjit; Kwan, Vu (Endoscopy, 2014)
Endosonography (EUS)-guided drainage of paragastric fluid collections using fully covered self-expanding metal stents (FCSEMS) is now a well-established procedure. Recently, new and specially designed lumen-apposing, fully-covered metal cystgastrostomy stents have been employed for this indication. In this case series, the use of these new stents for the drainage of malignant fluid collections in three symptomatic patients is described. Cases included a large pancreatic pseudocyst, secondary to underlying acute lymphoblastic leukemia, and two large collections of loculated ascites due to metastatic ovarian and cervical cancer, respectively. Technical success in inserting the new stents was achieved in all three patients, and resulted in symptomatic relief. There were no clinically significant complications directly attributed to the stents. These new lumen-apposing cystgastrostomy stents may provide a viable, minimally invasive, and effective alternative for drainage of malignant fluid collections, either for definitive treatment or for palliation of symptoms.